Influence of Timing on Surgical Outcomes for Acute Humeral Shaft Fractures - Ryogo Furuhata; Yusaku Kamata; Aki Kono; Yasuhiro Kiyota; Hideo Morioka (Advances in Orthopedics)
Surgical treatment for humeral shaft fractures has been reported to yield satisfactory results; however, there may be complications, such as delayed bone union, nonunion, iatrogenic radial nerve injury, and infection. The risk factors for postoperative complications remain largely unknown. This study aimed to investigate the influence of timing of surgery on the incidence of postoperative complications of acute humeral shaft fractures. We retrospectively reviewed 43 patients who underwent osteosynthesis for acute humeral shaft fractures between 2006 and 2020. The patients were divided into early (21 patients) and delayed (22 patients) treatment groups based on the timing of the surgical intervention (within or after four days). Outcomes were the incidences of complications (delayed union, nonunion, iatrogenic radial nerve injury, and infection) and postoperative fracture gaps. We evaluated the outcomes using plain radiographs and clinical notes. In addition, we performed subgroup analyses on outcomes in a subgroup of patients who underwent intramedullary nailing and one who underwent plate fixation. The frequency of delayed union was significantly higher in the delayed group (P=0.046), and the postoperative fracture gap size was also significantly greater in the delayed group (P=0.007). The subgroup analyses demonstrated a significant association between the increased incidence of delayed union and delayed surgical interventions only in the intramedullary nailing subgroup (P=0.017). This study suggests that performing surgery within four days after acute humeral shaft fracture is recommended to reduce the occurrence of delayed union, particularly in cases requiring intramedullary nailing fixation.